Changing trajectory of China–U.S. relations Background of current disputes - Przychodniak, Marcin (Asia in World Politics: Past, Present, and Future, 2021)
The purpose of the article is to analyze basic documents and statements on bilateral relations by both U.S. and China’s authorities. Main objective is to present a background for the U.S. – China relations based on analysis of these documents as well as political statements and experts opinions. Current misunderstandings between U.S. and China are mainly based on internal reasoning in order to secure the support of base electorate (Donald Trump) or keep alive the ideology of build-up and rejuvenation of a Chinese nation (Xi Jinping). Based on these assumptions the short-term perspective is rather negative with self-winding perspectives because of Trump’s determination and Chinese leadership growing feeling of necessity of a tougher response. The long-term perspective cannot exclude the possibility of reaching a compromise due to the transactional nature of Trump’s policies and China’s determination to keep the economy reforms standing which is impossible without U.S. involvement.